Pengaruh Tarif Air dan Kualitas Pelayanan terhadap Kepuasan Pelanggan PDAM Kabupaten Purworejo Cabang Pituruh - Hanung Dwi Oktaviandri (Progress, 2026)
The study aims to determine whether there is a positive and significant influence between water tariffs and service quality on customer satisfaction of Perumda Air Minum Tirta Perwitasari, Purworejo Regency, Pituruh Branch. Data collection uses observation, interview, questionnaire, literature study, and documentation techniques. The population in this study are customers of Perumda Air Minum Tirta Perwitasari, Purworejo Regency, Pituruh Branch who have subscribed for at least 1 (one) year. The sample used in this study was 100 people using purposive sampling technique. The data obtained were analyzed using multiple linear regression, coefficient of determination, t test and f test. There is a low relationship between water rates and customer satisfaction indicated by the correlation value between the two variables of 0.393 and there is a strong relationship between service quality and customer satisfaction indicated by the correlation value between the two variables of 0.672. The regression calculation between the water rate variable and service quality on customer satisfaction produces a regression of Y = 8.961 + 0.091 X1 + 0.566 X2 + e. Hypothesis testing produces a t count of the water rate variable smaller than the t table (0.756 < 1.661) and a significant value (0.451 > 0.05). Hypothesis testing produces a t count of the service quality variable (X2) greater than the table (7.305 > 1.661) and a significant value of (0.000 < 0.05). Hypothesis testing produces an f count greater than f table (40.376 > 3.09) and a significant value of (0.000 <0.05).